Analisis Kemampuan Koneksi Matematik dan Self Confidence Siswa SMP melalui Model Pembelajaran Think Pair Share - Alfiyah, Nisa Fitri; Rosdianti, Iis; Zanthy, Luvy Sylviana (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to describe the ability of mathematical connections and students' self confidence through the Think Pair Share (TPS) learning model. This research is a qualitative descriptive.. The instruments used in this study were the description test and self confidence questionnaire. From the results of the completion of the student description test, it was found that the level of mathematical connection ability through the Think Pair Share learning model for junior high school students is still relatively low. This is influenced by several factors, one of them is students' lack of understanding of the material and students are not able to transform the problem posed into the knowledge they have. This can be seen from the mistakes of students in working on the test description. Meanwhile, even though the test results of the mathematical connection description are still low, the scale of the students' self-confidence attitude is good enough at 60.96%.